"¿Tú tienes una little pumpkin?" Mixed noun phrases in Spanish-English bilingual children and adults. (August 2020) - Ramírez Urbaneja, Desirée
Objectives: This study investigates the switching of a noun or a determiner in mixed noun phrases, such as " una little pumpkin, " to test predictions from two theoretical frameworks, the Matrix Language Frame model (MLF) and the Minimalist Approach (MA) and examines whether there is a difference between child and adult code-switching (CS) patterns in order to understand children's acquisition of grammatical patterns in general. Methodology: All tokens of mixed noun phrases (NPs) were extracted from three bilingual child corpora and one bilingual adult corpus. The finite verb (matrix language) of each utterance was also analyzed to test predictions. Data and analysis: Four hundred sixty-one mixed NPs were extracted from 15 Spanish-English bilingual children and 14 Spanish-English bilingual adults. Findings: Results support both the MLF and the MA since in more than 80% of our data, the language of the determiner matched the language of the finite verb morphology and the language with the most phi features. Originality: This is the first study to compare children's and adults' mixed NPs, testing predictions from the MLF and MA theories. It also provides new evidence for the acquisition of CS constraints in early bilingual language development. Implications: This study demonstrates that, like adults, children's mixed NPs are subject to grammatical constraints. Some examples show that children produce mixed NPs immediately after hearing their caregivers produce the same NP, but in one language only. This supports the conclusion that children's mixed NP patterns follow generalized constraints and are not item-based imitations of what they hear. Limitations: Future research should more carefully examine the CS patterns of caregivers and members of the community with whom children interact to decipher the role of input. This would help answer the question of how children acquire CS patterns.